2011
DOI: 10.3109/09513590.2011.593662
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diabetes and ovariectomy on rat hippocampus (A biochemical and stereological study)

Abstract: Oxidative stress is one of the main reasons of both menopause and diabetes. So, it plays crucial role in the pathogeneses of that condition and disease. Therefore, the objective of the present study was to investigate the effects of menopause and diabetes upon the hippocampus using a rat model. Adult female Sprague Dawley rats (n = 24) were allocated randomly as follows; control (C group) ovariectomized (O group), diabetic (D group) and ovariectomy plus diabetic groups (DO group) (n = 6; in each group), respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…Various evidence prove that estrogen deficiency aggravates the risk of diabetes and associated complications. 4,34 In concurrence with this, we observed a severe impairment of memory in Ovx-Dia rats compared with ovariectomized and diabetic rats. Treatment with DPN and E 2 markedly improved-whereas treatment with PPT and insulin partially improved-learning and memory in these spatial memory tasks.…”
Section: Er Agonists In Postmenopausal Diabetessupporting
confidence: 83%
See 1 more Smart Citation
“…Various evidence prove that estrogen deficiency aggravates the risk of diabetes and associated complications. 4,34 In concurrence with this, we observed a severe impairment of memory in Ovx-Dia rats compared with ovariectomized and diabetic rats. Treatment with DPN and E 2 markedly improved-whereas treatment with PPT and insulin partially improved-learning and memory in these spatial memory tasks.…”
Section: Er Agonists In Postmenopausal Diabetessupporting
confidence: 83%
“…Deficiency of both estradiol and insulin contributes to the neurodegeneration process. 34 Estrogen acting through two ERs (ER-a and ER-b) regulates multiple functions in the central nervous system. 35 Studies of rodent brains have revealed that ER-a is the predominant ER in the hypothalamus and controls reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…Before beginning to work, the necessary strategy was determined by optical fractionator on the parts of the testis tissue [Altunkaynak et al 2012]. According to that, the section thickness and section sampling fraction were determined as 20 mm and 1/250, respectively.…”
Section: Optical Fractionator Methodsmentioning
confidence: 99%
“…13 Volume estimation with the cavalieri principle Volumetric evaluation of a structure that has any shape and size can effectively obtained by the Cavalieri principle. 14 An important rule of this origin is as follows: in order to get a impartial estimate of the volume of an objective, the objective must be cut to serial and parallel planes separate by a fixed interval 15,16 and using a point-counting grid for the area estimate of section profiles. The point density of the grid was designed to obtain a proper CE for the serial paraffin sections of the study.…”
Section: Tissue Sampling and Stereological Methodsmentioning
confidence: 99%